Brine discharges in coastal water - Yap, Wai Lei (2015)
A comprehensive experimental investigation for an inclined 45° dense jet in coflow ambient was carried out under a wide range of jet densimetric Froude number Fr and nominal Froude number NFr. The mixing behavior of the inclined 45° dense jet was observed. Planer Laser Induced Fluorescence (PLIF) was adopted as the measurement for the concentration field of the inclined dense jet. Based on the experimental results, the geometrical characteristics of the inclined dense jet were quantified. Normalized expressions for centerline peak height Zm/FrD, horizontal displacement of centerline peak point Xm/FrD and centerline peak dilution Sm/Fr were derived. Besides that, jet spread and concentration decay rate cm were also reported. Additional experiments involved different discharge nozzle diameters and different densities were conducted to examine their influence to the mixing of the inclined 45° dense jet. Two mixing regimes were identified, namely jet-dominated regime and coflow-dominated regime. The results show that even though Zm/FrD, Xm/FrD and Sm/Fr are influenced by NFr in coflow-dominated regime, they are independent of NFr in jet-dominated regime. Fr and NFr were found to have limited influence on the dimensionless cross-sectional concentration distribution and rate of concentration decay. Vertical spread of the inclined 45° dense jet can be restrained with large NFr.